The Effect of Investment Decisions and Dividend Policies on Company Value in the Food and Beverage Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Years 2021–2023 - Lestari, Bekti Wiji; Jumsar, Andhini Syafridha; Bintari, Wisang Candra; Waly, Nur Aeni; Wangsi, Mitta Muthia (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to help determine the effect of investment decisions and dividend policy on firm value in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX). The population of this study is from the 2021-2023 period using 90 data consisting of 30 food and beverage sector companies. The research method used is a quantitative approach with multiple linear regression analysis techniques which are processed using SPSS software. The results of this study indicate that investment decisions have a significant and positive effect on firm value. Meanwhile, dividend policy has no significant and negative effect on firm value. Simultaneously, investment decision variables and dividend policy have a significant effect on firm value.